Reviewing the Accountability Practices of Village Funds: Case Study from Indonesia - Andriani, Wiwik (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine the accountability of managing Nagari funds, including planning, implementing, reporting and accountability for managing village funds in Nagari Situjuah Batua. This study uses a qualitative approach to solve the phenomena raised. Data in this study were collected through several processes including in-depth interviews, observation, and documentation. The results of this study conclude that accountability for the management of Nagari funds in Nagari Situjuah Batua has been carried out from the planning, implementation, reporting and accountability stages in an appropriate manner and is also managed in an accountable manner so that the objectives of these funds are appropriate. The local government hopes that the Nagari funds can continue to be managed following the mandated community for the betterment of the village The novelty of this research is that it uses villages that have achievements at the local level as research objects